Determinants of Customers Using the Pegadaian Syariah Digital Service (PSDS) Application: Review of Islamic Business Ethics - Mukminatul, Diah; susanto, Is (Al-Mashrof: Islamic Banking and Finance, 2024)
Pegadaian Syariah Digital Service (PSDS) is used to make it easier for customers to carry out transaction processes and make payments.  This research aims to determine the influence of marketing strategies and the consumer environment on customers' decisions to use the Pegadaian Syariah Digital Service (PSDS) application at Pegadaian Syariah Bandar Lampung City, and to analyze transactions using the PSDS application from the perspective of Islamic Business Ethics.  The sample for this research is customers who use the Pegadaian Syariah Digital Service (PSDS) application, totaling 89 respondents.  The data collection technique uses a questionnaire via Google Form with multiple linear regression data analysis techniques using SPSS version 24 software. The results of this research show that marketing strategy and the consumer environment have a positive influence on customers' decisions to use the Pegadaian Syariah Digital Service (PSDS) application.